Slovenian nurses’ research utilization competence and received suport from nurse managers - Salminen, Leena; Kaučič, Boris Miha; Filej, Bojana; Leino-Kilpi, Helena; Katajisto, Jouko; Heikkilä, Asta (Nursing in the 21st Century, 2022)
SLOVENIAN NURSES’ RESEARCH UTILIZATION COMPETENCE AND RECEIVED SUPORT FROM NURSE MANAGERSIntroduction. Research utilization is the core of evidence-based practice. Nurse managers have an important role to support competence management and research utilization in nursing care.Aim. The aim of the study was to investigate the research utilization competence of Slovenian nurses working in hospitals and the received support from nurse managers related to research utilization. Research utilization competence comprises attitudes and the knowledge and skills.Methods. A descriptive, cross-sectional study design was used. The participants were nurses (n=154) from eight hospitals in Slovenia. Data was collected using the Competence in Research Utilization instrument and analyzed statistically.Results. Nurses’ attitudes were positive. Nurses’ appreciation of research utilization was higher than their readiness to commit themselves to research utilization. Nurses’ knowledge related to acquisition research evidence and reading and appraising research was rather limited even if they assessed their skills as above moderate. The received support from nurse managers related moderately to nurses’ research utilization skills.Conclusions. The research utilization competence of nurses is recommended to be strengthened with systematic competence management and support from nurse managers in clinical practice. Nurse managers can support nurses’ research utilization competence by encouraging them to participate in continuing education and by building systematic academic cooperation and networking between educators, researchers, and nurse clinicians.